Laser method and its effect on the oral mucous membrane in the context of the preprosthetic surgery* - Ryniewicz, Joanna; Ryniewicz, Wojciech; E. Loster, Jolanta; W. Loster, Bartłomiej (Journal of Stomatology, 2017)
Introduction. Various treatment methods are applied in the preprosthetic surgery. The most frequently used are lasers, standard excision of the lesion with a scalpel and with an electrocauter. Aim of the study. Comparison of the laser method (using the CO2 laser) with the standard method was chosen as the subject of the analysis. Material and method. The tests were conducted in 40 generally healthy patients of both sexes, aged 44-90 years with diagnosed stomatitis prothetica hyperplastica fibrosa (SPHF). Randomly divided patients formed two 20-people groups. In group I patients were subjected to the laser therapy, and in group II proliferative lesions were removed by excision with a scalpel and suture closure. Results. Differences in the clinical estimation of the healing process were indicated in both testing groups. In the course of the wound healing after the laser therapy, on the 30th day of observation, the presence of smooth scars was confirmed in 25% of patients, and scarless healing in 75% of patients. In patients undergoing the CO2 laser therapy, no astringent scars were observed.